Descritores estatísticos na caracterização das fricativas do Português Brasileiro: Características espectrais das fricativas - Ferreira-Silva, Audinéia [UNESP]; Pacheco, Vera; Cagliari, Luiz Carlos [UNESP] (Universidade Estadual de Maringa, 2015)
In this paper, we investigated the spectral characteristics of labiodental, alveolar and postalveolar fricatives of the Brazilian Portuguese in terms of place of articulation and vowel context. We measured the spectral characteristic of fricative noise using the analysis of four spectral moments (center of gravity, standard deviation, skewness and kurtosis). Our results indicated a significant effect of place of articulation and vowel context on values of spectral moments for fricatives of Brazilian Portuguese. The results show that the fricatives were well differentiated by the center of gravity and standard deviation more than the other spectral moments, skewness and kurtosis.
Statistical descriptors on the characterization of the Brazilian Portuguese fricatives: Spectral characteristics of fricatives
Keywords: Fricative; Place of articulation; Spectral characteristics